AIRING ETHNIC AND LINGUISTIC IDENTITIES THROUGH PUBLIC MEDIA COMIC PERFORMANCES: CHALLENGING AND REINSCRIBING NORMATIVE IDEOLOGIES - Garcez, Pedro de Moraes (Revista da Anpoll, 2016)
This essay discusses double voicings in heteroglossic public media comic performances of ethnic and linguistic identities. The objective is to show an example of how airing ethnic-linguistic identities through media comic performances brings to the open previously silenced, sensitive issues for necessary public debate, also providing a rich field for research on contemporary sociolinguistic questions. The example explored here is a comparative illustration, presented at an academic seminar, between the data analyzed by Jaffe (2000), featuring comic bilingual performances in Corsica, and comic radio and television performances featuring a German-Brazilian character. First, the multi-site, multimedia academic seminar course is introduced. Next, four illustrative videos, shown during the seminar presentation as a counterpoint to Jaffe’s data, are described, two of which spotlight D. Heda, a fictional German-Brazilian comic character. Further material is examined here – an interview with the radio journalist who created and performs D. Heda, in which he presents his radio program as validating German-Brazilian identities. This is briefly contrasted with comments by a course participant arguing such humor is disparaging of German-Brazilians. Finally, in light of recent studies of similar heteroglossic public media comic performances, the tensions these performances may create between challenging and reinscribing normative ideologies are discussed. This work is licensed under a Creative Commons Attribution 3.0 License.